Design and Discovery of Some Novel Chalcones as Antioxidant and Anti‐Inflammatory Agents via Attenuating NF‐κB. Issue 1 (10th December 2015) - Chu, Jun; Guo, Chun‐Liang
Abstract : Concerning the role of antioxidant and anti‐inflammatory agents for hepatic fibrosis patients, the current study deals with the development of novel chalcone derivatives5a–i via efficient synthetic methodology in a two‐step reaction involving Claisen–Schmidt condensation. The obtained target analogs were screened for in vitro antioxidant activity by various methods (H2 O2, DPPH, ferrous reducing power, and nitric oxide), where they exhibit considerable radical scavenging activity. These compounds were also evaluated for inhibitory potency against NF‐κB activation induced by LPS for the determination of their anti‐inflammatory activity. The inhibition values indicate that the entire set of compounds efficiently inhibits the NF‐κB activation provoked by LPS. Among the series, compound5i was identified as the most potent inhibitor of NF‐κB, with a relative NF‐κB activity of 1.12 ± 0.53. It also inhibits various inflammatory mediators, such as TNF‐α, IL‐1β, IL‐6, and PGE2 . Abstract : Novel chalcone derivatives5a –i were synthesized by a two‐step reaction involving Claisen–Schmidt condensation and screened for their in vitro antioxidant activities. All compounds exhibit considerable radical scavenging activity. The entire set of compounds also efficiently inhibit the NF‐κB activation provoked by LPS.